Organization of Female Turn Taking Pattern inUrdu Conversations (Journal of Asian Development Studies, 2024)
This article looks at the norms of turn-taking in Urdu discourse as an aspect of femalecommunication tactics. A "turn-talking game" is what Tannen (1984) describes communication asbeing. This study aims to discover the structure of female turn-taking patterns in Urduconversations and the distribution of turns within them. While the data does demonstrate thatspeakers switch and turn size and ordering might fluctuate, the majority of the time, just one sideis speaking at a time. Different methods are employed to distribute turns, and those transitions aremeticulously coordinated. The research also considers overlapping and pauses in Urduconversation, but they do not distort the turn-taking pattern. Instead, these elements are ruledpreserving.